Endoscopic septotomy as a treatment for leaks after sleeve gastrectomy: Meeting presentations: Digestive Disease Week 2019 - Diaz, Ramon (Endosc Int Open, 2020)
Background and study aims  Sleeve gastrectomy (LSG) is the most commonly performed bariatric procedure in the world. Leaks are the most feared complications after this procedure. Endoscopic septotomy has been described as a resolution technique that could be useful in the setting of late and chronic leaks. We present our experience in the management of gastric leaks with this advanced endoscopic technique. Patients and methods  Retrospective review of patients who have been admitted to our hospital from January 2016 to December 2018. Results  Five patients were found. All had their index surgery in outside hospitals. The average age was 51 years (range 40 – 69), and four patients were female. Mean time from LSG to leak presentation was 15 days (range 7 – 25). Mean time from leak presentation to septotomy procedure was 61 days (range 21 – 110). All patients were treated with sleeve dilatation before septotomy using endoscopic achalasia balloons. Mean procedure time was 79 minutes (range 55 – 125). Success was achieved in 80 % of patients, and no complications related to the procedure were identified. One patient underwent total gastrectomy for definitive management. Mean follow-up time was 14.25 months (range 6 – 26), and the average time for fistula closure was 60.25 days. Conclusion  Endoscopic septotomy is safe and effective for management of chronic leaks after LSG. Associated non-selective dilatation may be a crucial step to allow distal patency and axis rectification for appropriate leak closure.